2010
DOI: 10.4314/bajopas.v2i1.58475
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility pattern of <i>Aeromonas hydrophila</i> among patients presented with diarrhea attending two teaching hospitals in northern, Nigeria

Abstract: A total of one hundred and twenty eight (128) stool samples were collected from patients attending Ahmadu Bello University Teaching Hospital Zaria and Aminu Kano Teaching Hospital Kano, and screened for the presence of Aeromonas hydrophila infection. Out of the one hundred and twenty eight samples analyzed 4 (3.12%) were found positive for Aeromonas hydrophila infection. Antibioticsusceptibility testing of Aeromonas hydrophila isolated showed that all the 4 (100%) isolates were sensitive to Colistin and Ceftaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This is consistent with some previous studies [30][31]. However, in contrast to Rogo et al [25] who reported only a few species were resistance to Augmentin in their study, although, Imipenem has been reported to be effective for treatment of Aeromonas infection [32], in the present study all the isolates were resistant to Imipenem. Four isolates of A. hydrophila in this study were resistant to cefazolin and gentamycin but susceptible to ciprofloxacin and tetracycline.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with some previous studies [30][31]. However, in contrast to Rogo et al [25] who reported only a few species were resistance to Augmentin in their study, although, Imipenem has been reported to be effective for treatment of Aeromonas infection [32], in the present study all the isolates were resistant to Imipenem. Four isolates of A. hydrophila in this study were resistant to cefazolin and gentamycin but susceptible to ciprofloxacin and tetracycline.…”
Section: Resultssupporting
confidence: 92%
“…In this study, Aeromonas hydrophila was the only species isolated and is from the diarrheic stool samples. Several studies have shown a similar preponderance of the species [22][23][24][25]. The prevalence rate of 3.5% from diarrheic stool samples in the present study is consistent with that of Rogo et al [25] who reported a prevalence of 3.12% in 128 patients attending Ahmadu Bello University Teaching Hospital (ABUZTH) and Aminu Kano Teaching Hospital (AKTH) but less than the 13% reported by Nzeakor and Okafor [26] in Nigeria and 12.8% reported by Samie et al [27] in South Africa.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Aeromonas dhakensis is pathogenic in fish (Soto Rodriguez et al, 2013) and human (Rogo et al, 2009). Aeromonas are responsible for ulcerative disease outbreaks in Mtera Dam (Shayo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%